New Composite Indexes through Factor Analysis Simplifying the Interpretation of Health-Related Quality of Life Outcomes of Surgical Adolescent Idiopathic Scoliosis Patients Completing both Scoliosis Research Society-22 and SAQ Questionnaires Longitudinally - Wai-Wang Chau; Bobby Kin-Wah Ng (Journal of Orthopedics, Traumatology and Rehabilitation)
Background: Both Scoliosis Research Society-22 (SRS-22) questionnaire (on patients’ outcome) and Scoliosis Appearance Questionnaire (SAQ) (on patients’ appearance) were well-accepted and well-validated patient-reported outcome measures. Our center administered both to severe adolescent idiopathic scoliosis (AIS) patients who underwent spinal correction. In view of a total of 14 (9 + 5) major domain scores from both questionnaires, this study attempted to develop new composite indexes using factor analysis. Materials and Methods: All operated AIS patients within the years 2014 and 2016 were recruited. Patients were administered both SRS-22 questionnaire and SAQ before surgery, before discharge after surgery, 1 year after surgery, and 2 years after surgery. Factor analysis without rotation was carried out and identified a total of 12 factorable domains. Factor analysis with rotation on the 12 domains was followed. Descriptive statistics and reliability analysis on the loaded factors (composite indexes) were calculated. Results: There were 135 severe AIS patients recruited in this study, of which 74.1% were female, and the mean age at operation was 15.97. Two factors were yielded after factor analysis (KMO = 0.633 and Bartlett’s Test of Sphericity < 0.001) with orthogonal rotation. “Trunk symmetry and health-related quality of life (HRQOL)” loaded with 2 SAQ and all 5 SRS-22 scores, and 5 SAQ scores in “Body appearance.” Reliability tests showed very strong internal consistency. Skewness and kurtosis showed data in both indexes were normally distributed. Conclusions: Two composite indexes “Trunk symmetry and HRQOL” and “Body appearance” were loaded after factor analysis of 12 domains from SRS-22 and SAQ. Both composite scores were reliable and normally distributed. The development of the new composite indexes “Trunk symmetry and HRQOL” and “Body appearance” simplifies result interpretation without losing the characteristics of SRS-22 and SAQ. Results can be interpreted in the same direction.